KEDUDUKAN HUKUM ANAK AKIBAT HASIL PERKAWINAN CAMPURAN ANTARA WARGA NEGARA INDONESIA DAN JERMAN MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - AXELCIUS ODIE FIRMANTHO NIM. A1012191069 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac The position of children in mixed nationality marriages that occur in Indonesia is a marriage between an Indonesian woman and a foreign man. Between the two relations, they remain subject to two different sovereigns. Likewise when they have a child, based on the old law, when the child is born into the world he has followed the nationality of his father, without the right to choose his own nationality, and this creates a sense of injustice on the part of Indonesian women, because if one day something happens If there is a problem or divorce between the parents, the mother will feel very disadvantaged because she cannot have custody of her child and most of the cases that occur are the child being taken away by the father, and the mother cannot do anything about it. With so many cases that were detrimental to these Indonesian women, a new law was made, namely Law number 12 of 2006 which replaced Law number 62 of 1958 which was considered to lack the value of justice, and was no longer appropriate. again with the development of society which is closely related to Law Number 1 of 1974 concerning Marriage.So the problem is